Formaldehyde surrogates in multicomponent reactions - Attorresi, Cecilia I.; Ramírez, Javier A.; Westermann, Bernhard (Beilstein Journal of Organic Chemistry, 2025)
Formaldehyde emerges as a cornerstone in multicomponent reactions, mainly prized for its robust reactivity. Yet, alongside these beneficial traits, this highly reactive C1-building block raises concerns, primarily regarding its toxicity. One notable issue is the challenge of controlling the formation of undesired byproducts during its reactions. This review explores alternative C1-building blocks that serve as surrogates for formaldehyde, aiming to mitigate some of the challenges associated with its use in multicomponent reactions. By identifying these alternatives, toxicity concerns and improved reaction control can be addressed, paving the way for more efficient and sustainable synthetic methodologies.
Keywords: cascade reactions; formaldehyde surrogates; green chemistry; heterocycles; multicomponent reactions